Liberalization of the Capital Account : Experiences and Issues - Mathieson, Donald (IMF Working Papers; Working Paper, 1992)
This paper reviews the experience with capital controls in industrial and developing countries, considers the policy issues raised when the effectiveness of capital controls diminishes, examines the medium-term benefits and costs of an open capital account, and analyzes the policy measures that could help sustain capital account convertibility. As the effectiveness of capital controls eroded more rapidly in the 1980s than in earlier periods, new constraints were placed on the formulation of stabilization and structural reform programs. However, experience suggests that certain macroeconomic, financial, and risk management policies would allow countries to attain the benefits of capital account convertibility and reduce the financial risks created by an open capital account.